Lila an inquiry into morals - Pirsig, Robert M. (New York, New York Bantam Books, 1992)
Phaedrus is traveling in a sailboat down the Hudson River when he meets Lila, a woman who threatens to disrupt his life and causes him to reexamine his personal philosophy.